Comparative Study on the Preservation Efficacy of Rosemary Extracts and Conventional Preservatives on Tomatoes. - Namanya, Jonan (Kabale University, 2025)
Tomatoes, a vital agricultural commodity, are prone to significant post-harvest losses due to their high perishability. Traditional preservation methods like synthetic chemical preservatives have been effective but raise health concerns. With growing consumer demand for natural and safer food products, rosemary (Rosmarinus officinalis) has emerged as a promising natural preservative due to its antioxidant and antimicrobial properties. However, its comparative efficacy with conventional preservatives is underexplored. This study presents a comparative analysis of the preservation efficacy of rosemary extracts versus conventional preservatives (sodium benzoate and bacterimycin) on tomatoes. The research aimed to assess the effectiveness of rosemary extracts in maintaining the physiological quality, shelf life, and overall condition of tomatoes during a 14-day storage period. This study evaluated key indicators such as color retention, weight loss, and shelf life in tomatoes treated with rosemary extract at concentrations of 0.5%, 1.0%, and 1.5%, alongside conventional preservatives and an untreated control group. The methodology involved visual ratings, and measurements of percentage weight loss. Results indicated that rosemary extract, particularly at 1.0% and 1.5% concentrations, significantly outperformed conventional preservatives, leading to superior color retention and reduced weight loss, with spoilage delayed by up to 12 days. These findings suggest that rosemary extract offers a viable, eco-friendly alternative to synthetic preservatives. The study concludes that rosemary extract is an effective means of preserving tomato quality and recommends further research to explore its application across various fruits and storage conditions, potentially enhancing food preservation strategies.